2020
DOI: 10.1167/iovs.61.3.44
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Reveals α-2-HS-Glycoprotein as a Key Early Extracellular Matrix Protein for Conjunctival Cells

Abstract: Purpose To determine the composition of extracellular matrix (ECM) proteins secreted by a conjunctival epithelial cell line and to identify components that aid conjunctival epithelial cell culture. Methods Human conjunctival epithelial cell line (HCjE-Gi) cells were cultured in serum-free media and their ECM isolated using ammonium hydroxide. Growth characteristics were evaluated for fresh HCjE-Gi cells plated onto ECMs obtained from 3- to 28-day cell cultures. Mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…According to further analysis of the gene expression between the dead chRCC patients ( n = 9) and the surviving chRCC patients ( n = 56) (Figure 9A), only the AHSG gene survived significantly less in chRCC contrasted to normal samples ( p < 0.05) (Figure 8), suggesting that AHSG may be a potential biomarker associated with prognosis of chRCC. The top 20 proteins interacting with AHSG by GeneMANIA were partially associated with tumor development or tumor suppression, which also suggests that AHSG is a potential key gene for chRCC 26,27,29,30,33–35,37,38 …”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…According to further analysis of the gene expression between the dead chRCC patients ( n = 9) and the surviving chRCC patients ( n = 56) (Figure 9A), only the AHSG gene survived significantly less in chRCC contrasted to normal samples ( p < 0.05) (Figure 8), suggesting that AHSG may be a potential biomarker associated with prognosis of chRCC. The top 20 proteins interacting with AHSG by GeneMANIA were partially associated with tumor development or tumor suppression, which also suggests that AHSG is a potential key gene for chRCC 26,27,29,30,33–35,37,38 …”
Section: Discussionmentioning
confidence: 90%
“…The result showed that the top 20 proteins interacting with AHSG (Figure 9B ) mainly functioned in tumor suppressor, signal transduce, cancer development. 26 , 27 , 29 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BM is a dynamic structure the composition of which changes not only during development, but also with age and following repair of injury. Although not measured in vivo, in vitro studies using a human immortalized conjunctival cell line (HCjE) showed changes to the composition of the ECM over a twenty-eight day culture period (54). Using mass spectrometry, the whole proteome of the ECM was studied and proteins such as -2-HS-glycoprotein were identified in the conjunctival ECM.…”
Section: Other Glycoproteins and Proteoglycansmentioning
confidence: 99%